An unusual case of xanthogranulomatous orchitis: A tumor mimic - Kavita Somani; Pretty Singh; Siddhant Verma; Tanmai Tandon (Apollo Medicine)
Xanthogranulomatous inflammatory reaction is an uncommon nonneoplastic disease process, which is an even rarer entity in testicles. We present a similar case report of a 20-year-old male with a testicular swelling and a provisional clinical diagnosis of a testicular neoplasm. We hence present this case in view of its rarity and its nature to deceptively mimic a neoplasm.